APPLICATION OF CHICKEN EGG SHELL POWDER ON VARIETIES OF PEANUT (Arachis hypogaea L) - Murniati, Nely; Apriyanti, Apriyanti; Bimasri, John; Sutejo, Sutejo (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Utilization of organic waste as an alternative fertilizer is one of the efforts to improve sustainability in agriculture. Egg shells, as household waste rich in calcium carbonate (CaCO₃), have great potential to be used as soil ameliorant and a source of nutrients for plants. The purpose of the study was to examine the benefits of chicken egg shell waste in peanut cultivation. The study was conducted in Watervang Village, Lubuklinggau City at an altitude of 113.59 meters above sea level, from March to June 2024, using a factorial Randomized Block Design experimental method consisting of 3 group. Treatment of chicken egg shell powder doses: 0.2, 0.6, and 1.0 tons-ha, and peanut varieties consisting of giraffe variety, bison variety and talam1 variety. The study consisted of 27 units, each unit consisting of 3 sample plants. The parameters observed consisted of the number of branches, flowering age, number of pods per plant, weight of pods per plant, weight of seeds per plant, weight of 100 seeds and soil pH. Data were analyzed by Analysis of Variance (Anova), the effect of treatment was analyzed by Honestly Significant Difference Test (HSD), to determine the level of accuracy, the Coefficient of Diversity test was carried out. The results of the study of the application of chicken egg shell powder at a dose of 1.0 tons-ha. The results of the study of the application of egg shell powder at a dose of 1.0 tons-ha showed an increase in peanut production. The use of the Talam 1 variety was able to provide better growth and production. Between the application of chicken egg shell doses and varieties did not show any significant interaction. Keywords: egg shells; peanuts; soil pH; varieties.